Phase II Study of Sorafenib and Bortezomib for First‐Line Treatment of Metastatic or Unresectable Renal Cell Carcinoma. (16th March 2015) - Rao, Arpit; Lauer, Richard
Abstract : Background: Sorafenib is an orally active multikinase inhibitor, and bortezomib is a proteasome inhibitor that affects multiple signaling pathways. Sorafenib has clinical activity in renal cell carcinoma (RCC), whereas bortezomib has demonstrated activity against RCC cell lines in vitro, with in vitro studies showing synergism between the two agents in the induction of apoptosis in neoplastic cell lines. In this phase II study, we explored the efficacy and toxicity of this regimen. Methods: Adult patients with cytologically confirmed clear cell RCC with no prior chemotherapy, Zubrod performance status of 0–1, serum creatinine <1.5 mg/dL, and normal liver function tests were treated with sorafenib 200 mg orally b.i.d. with bortezomib 1 mg/m 2 intravenously on days 1, 4, 8, and 11 every 21 days. Treatment was continued until disease progression or unacceptable toxicity. The primary objective was median progression‐free survival (PFS) of at least 70 weeks. Results: Seventeen patients were enrolled between April 2011 and January 2013. Median age was 62 years (range: 44–75 years). Four of 17 patients had known brain metastasis on enrollment. Median number of cycles was 4 (range: 1 to ≥45). No patient had complete response, 1 had partial response, 12 had stable disease, and 4 had progressive disease (response rate of 6%; 95% confidence interval: 0%–29%) with treatment. Median PFS was 13.7 weeks, and median overall survival was 110 weeks. The study was halted for futility. Conclusion: The combination of sorafenib and bortezomib was well tolerated; however, response rate and PFS were comparable to sorafenib monotherapy. This regimen is not recommended for further development. Abstract : 摘要 背景 . 索拉非尼是口服的活性多激酶抑制剂，硼替佐米是可影响多个信号通路的蛋白酶体抑制剂。索拉非尼对肾细胞癌（RCC）具有临床活性，而硼替佐米则在体外RCC细胞系中被证实具有抗RCC活性，同时在体内研究提示这两个药物在诱导肿瘤细胞系凋亡方面具有协同作用。我们在本项II期研究中探索了这一方案的有效性和毒性特征。 方法 . 患者入选标准如下：成年，经细胞学确诊为透明细胞型RCC，既往未接受过化疗，Zubrod体能状态0 ∼ 1，血清肌酐水平< 1.5 mg/dL，肝功能检验结果正常。治疗方案：索拉非尼200 mg口服，每天两次；硼替佐米于第1、4、8、11天1 mg/m 2 静脉输注，21天为一周期。治疗持续至疾病进展或发生不可接受的毒性事件。主要终点是中位无进展生存（PFS）至少达到70周。 结果 . 2011年4月至2013年1月共纳入17例患者。中位年龄62岁（范围：44 ∼ 75岁）。4/17例患者在进入研究时已知发生脑转移。中位治疗周期为4个（范围：1 ∼ ≥ 45）。接受治疗的患者中，无人达到完全缓解，1例部分缓解，12例疾病稳定，4例发生疾病进展（缓解率为6%，95%可信区间：0 ∼ 29%）。中位PFS为13.7周，中位总生存为110周。研究因无获益而停止。 结论 . 索拉非尼联合硼替佐米方案耐受良好，但缓解率和PFS与索拉非尼单药治疗相似。不建议对该方案进行进一步研究。 The Oncologist 2015;20:370–371